Compression behaviour of bio-inspired honeycomb reinforced starfish shape structures using 3D printing technology - Syed Abdullah, Syed Ahmad Saufi; Mohamed Yusoff, Mohd Zuhri; Mohammad Reza, Lalegani Dezaki; Salit, Mohd Sapuan; R. A., Ilyas; As'arry, Azizan; Mohd Ariffin, Mohd Khairol Anuar; M., Bodaghi (Multidisciplinary Digital Publishing Institute, 2021)
The bio-inspired structure (e.g., honeycomb) has been studied for its ability to absorb energy and its high strength. The cell size and wall thickness are the main elements that alter the structural ability to withstand load and pressure. Moreover, adding a secondary structure can increase the compressive strength and energy absorption (EA) capability. In this study, the bio-inspired structures are fabricated by fused deposition modelling (FDM) technology using polylactic acid (PLA) material. Samples are printed in the shape of a honeycomb structure, and a starfish shape is used as its reinforcement. Hence, this study focuses on the compression strength and EA of different cell sizes of 20 and 30 mm with different wall thicknesses ranging from 1.5 to 2.5 mm. Subsequently, the deformation and failure of the structures are determined under the compression loading. It is found that the smaller cell size with smaller wall thickness offered a crush efficiency of 69% as compared to their larger cell size with thicker wall thickness counterparts. It is observed that for a 20 mm cell size, the EA and maximum peak load increase, respectively, when the wall thickness increases. It can be concluded that the compression strength and EA capability increase gradually as the cell size and wall thickness increase.